Binding mode and free energy prediction of fisetin/β-cyclodextrin inclusion complexes - Nutho,B. (Beilstein-Institut Zur Forderung der Chemischen Wissenschaften, 2015)
© 2014 Nutho et al; licensee Beilstein-Institut. In the present study, our aim is to investigate the preferential binding mode and encapsulation of the flavonoid fisetin in the nanopore of β-cyclodextrin (β-CD) at the molecular level using various theoretical approaches: molecular docking, molecular dynamics (MD) simulations and binding free energy calculations. The molecular docking suggested four possible fisetin orientations in the cavity through its chromone or phenyl ring with two different geometries of fisetin due to the rotatable bond between the two rings. From the multiple MD results, the phenyl ring of fisetin favours its inclusion into the β-CD cavity, whilst less binding or even unbinding preference was observed in the complexes where the larger chromone ring is located in the cavity. All MM- and QM-PBSA/GBSA free energy predictions supported the more stable fisetin/β-CD complex of the bound phenyl ring. Van der Waals interaction is the key force in forming the complexes. In addition, the quantum mechanics calculations with M06-2X/6-31G(d,p) clearly showed that both solvation effect and BSSE correction cannot be neglected for the energy determination of the chosen system.